Analisis Penerapan Prinsip-Prinsip Ekonomi Islam Dalam Bisnis Retail Di Perusahaan PTPN IV Medan - Agna Sabrina; Andri Soemitra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
PTPN IV Medan Company is a company operating in the plantation sector in Medan, Indonesia. As a company operating in the business sector, PTPN IV Medan also has a retail business division which is an important part of its operational activities. This research is the result of qualitative research by raising the problem of how to apply Islamic economic principles in the PTPN IV Medan company. This type of research method is qualitative research using a descriptive approach and library research. As for the data sources in this research, the primary data is interviews with related parties, namely employees who work at the PTPN IV Medan company, while the secondary data is data obtained through reports regarding the PTPN IV Medan Company. In this context, it is important to evaluate the extent to which this company applies Islamic economic principles in its retail business. This analysis can also provide insight into the effectiveness and success of implementing Islamic economic principles in the company's retail business.